KONTRIBUSI DINAS SOSIAL DALAM UPAYA PENGENTASAN KEMISKINAN DI KABUPATEN JEMBER - Karisma Agustiya; Desy Wulandary; Nur Faizah Badriyatun Nufus; Hikmatul Hasanah (JURNAL PENGABDIAN MANDIRI, 2024)
Contribution is defined as an effort or contribution that provides benefits or added value to something. Contributions in the social sphere can be in the form of voluntary actions, donations or participating in social activities to improve community welfare. This research and service aims to determine the impact of the contribution of the Social Service in efforts poverty alleviation in Jember Regency. The research method used is a qualitative research method with a descriptive approach. The topics used are efforts, goals, obstacles and solutions as well as social service programs in the Jember Regency Social Service. The findings show a significant reduction in the level of poverty in the Jember Regency area. Conclusions from the research and service of the Social Service can be an effective instrument in alleviating poverty with a focus on community economic empowerment. The results of this research and service provide the basis for developing policies that are more effective in reducing poverty and provide inspiration for institutions to design similar programs in areas with similar poverty challenges